La fonte nascosta: inventio e dissonanza tra Paulhan, Desnos e Hopper (ENTHYMEMA, 2022)
The article begins with the inherent automatism of the use of common sayings in a wider interpretation in order to clarify some of the most fundamental points of reflexion of Jean Paulhan who was director of the NRF in the middle years of the twentieth century. Furthermore, Henri Meschonnic’s contribution will be taken into account. The following remarks on rhythm which have already been used by Paulhan as well as Dadaists and surrealists lead us to the rediscovery of the intersubjective aspect which, as hidden sources of the base of common sayings, allow us to discuss and revitalize those clichés. This reworking gives the possibility to observe the prejudices and the hidden automatisms in language. The various points which link the hidden source from which common sayings originate, the défigement belonging to the poet Robert Desnos and the canvasses painted by Edward Hopper, will come to light.
Keywords: Paulhan; Desnos; Proverb; Inventio; Défigement